New methods of concurrent checking - Gössel, Michael. (Frontiers in Electronic Testing,, 2008)
New Methods of Concurrent Checking is the ultimate reference to answer the question as to how the best possible state-of-the-art error detection circuits can be designed. The most effective methods of concurrent checking for digital circuits are comprehensively described which were developed in the last 15 years. Some of the methods are published for the first time. How concurrent checking can be combined with soft error correction is also shown for the first time. This book is invaluable in considering the design of reliable systems in the emerging Nanotechnologies with an associated growing number of transient faults. Written by a team of two leading experts and two very successful young former PhD students, New Methods of Concurrent Checking describes new methods of concurrent checking, such as partial duplication, use of output dependencies, complementary circuits, self-dual parity, self-dual duplication and others. A special chapter demonstrates how the new general methods of concurrent checking can be more specifically applied to regular structures to obtain optimum results. This is exemplified for all types of adders up to 64 bits with a level of detail never before presented in the literature. The clearly written text is illustrated by about 100 figures. New Methods of Concurrent Checking is approved in many university courses for graduate and undergraduate students, and it is of interest to students and teachers in electrical engineering and computer science, researchers and designers and all readers who are interested in the design and the understanding of reliable circuits and computers.